2022
DOI: 10.3390/foods11203175
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Phytochemical Profile and In Vitro Bioactivity of Beverages Based on the Unprocessed and Extruded Sesame (Sesamum indicum L.) Seed Byproduct

Abstract: In this research functional beverages based on the unprocessed and extruded sesame seeds byproduct were fabricated; phytochemical profile, antioxidant, antidiabetic, and hypoglycemic potential were evaluated. Twenty-four phytochemical compounds were identified in total in both beverages; fourteen of the phytochemical compounds were not modified by the extrusion process. Seventeen of the 24 compounds were identified in the unprocessed sesame seeds byproduct flour beverage−10% (UB10) and 21 in the extruded sesam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The authors demonstrated that along with anthocyanins and other phenolics, proteins also exhibited an inhibition effect on α-glucosidases [145]. The extrusion of sesame seeds by-product determined the increase in α-amylase and α-glucosidase enzymes inhibition effects of the beverage prepared from it, with a more pronounced trend on α-glucosidase due to the affinity of phenolics from sesame toward this enzyme [146]. Hemp seeds presented a greater inhibitory effect on α-glucosidase enzyme after extrusion, a trend that was correlated with the phenolics content and antioxidant activity [71].…”
Section: Effects Of Extrusion On the Biological Activitymentioning
confidence: 99%
“…The authors demonstrated that along with anthocyanins and other phenolics, proteins also exhibited an inhibition effect on α-glucosidases [145]. The extrusion of sesame seeds by-product determined the increase in α-amylase and α-glucosidase enzymes inhibition effects of the beverage prepared from it, with a more pronounced trend on α-glucosidase due to the affinity of phenolics from sesame toward this enzyme [146]. Hemp seeds presented a greater inhibitory effect on α-glucosidase enzyme after extrusion, a trend that was correlated with the phenolics content and antioxidant activity [71].…”
Section: Effects Of Extrusion On the Biological Activitymentioning
confidence: 99%